Psychology and Philosophy
XVIII, 336 p.
Keywords: Psychology and Philosophy provides a history of the relations between philosophy and the science of psychology from late scholasticism to contemporary discussions. The book covers the development from 16th-century interpretations of Aristotle’s De Anima, through Kantianism and the 19th-century revival of Aristotelianism, up to 20th-century phenomenological and analytic studies of consciousness and the mind. In this volume historically divergent conceptions of psychology as a science receive special emphasis. The volume illuminates the particular nature of studies of the psyche in the contexts of Aristotelian and Cartesian as well as 19th- and 20th-century science and philosophy. The relations between metaphysics, transcendental philosophy, and natural science are studied in the works of Kant, Brentano, Bergson, Husserl, Merleau-Ponty, Wittgenstein, and Davidson. Accounts of less known philosophers, such as Trendelenburg and Maine de Biran, throw new light onthe history of the field. Discussions concerning the connections between moral philosophy and philosophical psychology broaden the volume’s perspective and show new directions for development. All contributions are based on novel research in their respective fields. The collection provides materials for researchers and graduate students in the fields of philosophy of mind, history of philosophy, and psychology.